The state and religious violence in Indonesia: minority faiths and vigilantism - Suryana, A'an ca. 20./21. Jh. (Routledge contemporary Southeast Asia series, 2020)
Escalating Heresy Campaign against Ahmadiyah and Shi'a Communities -- State Official's Entanglement with Vigilante Groups -- The Judiciary and the Law -- Local Bureaucrats -- The President -- Conclusion : State Capacity and Communal Violence against Minority Faiths.